In Vivo Study of Diethylstilbestrol Teratogenicity on Mouse Embryo: Teratogenicity of diethylstilbestrol - Sabzevari, Omid; Etemadi, Behnaz; Marzban, Hassan; Ostad, Syyed Nasser (Iranian Journal of Pharmaceutical Sciences, 2005)
Diethylstilbestrol (DES) was widely used in the past, as the morning after contraception, but its application became extremely limited due to several complications including delayed clear cell adenocarcinoma in female infants. However, the use of DES increased during the past decade for hormone replacement therapy. The aim of this study was to investigate possible teratogenicity of this synthetic oestrogen. The experiment was conducted on N-MRI mice. Various concentrations of DES were administered i.p. to pregnant animals throughout the period of organogenesis (days 9 and 10 of pregnancy). The control group received ethanol as vehicle. Pregnancy was terminated on the 18th day by cervical dislocation. The embryos were then removed and fixed in Bouin’s solution, and parameters currently used in teratogenic studies were assessed. Severe embryo toxicity score was observed following the application of DES at doses of 200 and 400 mg/kg (71.4% and 83.6%, respectively). The weight and the average size of some of the examined parameters were markedly decreased by embryological observation. Furthermore, the size of derm and mosaic cells of urinary bladder, shortening in the length of femur, and abnormal disposition of calcium compound in embryos were markedly different in the treated mice.